Body and reality : an examination of the relationships between the body proper, physical reality, and the phenomenal world starting from Plessner and Merleau-Ponty /: an examination of the relationships between the body proper, physical reality, and the phenomenal world starting from Plessner and Merleau-Ponty. ([2018]) - Buuren, Jasper van, 1974-
No abstract available